Modelagem e simulação de eventos discretos de uma linha de produção de insumos para diagnósticos - Pinto, Andrei Ferreira (2018)
The dynamic and highly competitive scenario generated by the rapid development of the global molecular diagnostics market has been pushing companies toward the expansion of their activities and remodelling their growth strategies. However, the high risk associated with investments in manufacturing infrastructure requires prudence and accurate planning in order to succeed in medium and long terms. Systems modelling and computer simulation play an important role in reducing this risk, as it allows experimentation of countless system configurations and complete analysis on the effects of modifications in existent facilities without requiring changes in the real system. The present study describes the construction and validation of a discrete event simulation model representing the part of the Molecular Biology Institute of Paraná facility responsible for manufacturing HIV/HCV NAT and HBV NAT amplification modules for in vitro diagnosis of HIV, hepatitis B and hepatitis C infections. The virtual model intends to predict the facility maximum capacity in different configurations. The model validation was based on the comparison between simulated performances and real data extracted from 29 production dossiers related to each of the five processes considered, indicating less than 10% deviation in total process time in all cases. Furthermore, the capacity analysis revealed maximum monthly production of 7667 modules adopting two manufacturing periods (four hours each) per day, whereas a single six hours manufacturing cycle per day indicated capacity of 6667 modules per month. Thus, both manufacturing schemes are able to reach production volumes considerably higher than the national demand: 263% higher in the four hours arrangement and 216% in the six hours proposal. The results found in this thesis suggest possibilities of meeting larger production demands or including new processes in the facility without affecting the supply of well-established processes.